Human Capital and the Involvement of Urban B40 Women in The Informal Sector in Sabah - Roslinah Mahmud; Dayangku Aslinah Abd Rahim; Beatrice Lim Fui Yee; Khairul Hanim Pazim @ Fadzim; Siti Hajar Samsue; Caroline Geetha (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
Human capital typically refers to an individual's possession of attributes such as knowledge, skills, and professional experience. The cumulative levels of education, skills, and diverse knowledge contribute to an economic value that can enhance an individual's overall productivity. The augmentation of human capital assets not only has the potential to bolster personal savings and income but also serves as a significant factor in fostering the economic involvement of women, notably in the informal sector, to elevate their families' quality of life. The informal sector encompasses economic activities conducted by entities or entrepreneurs that are not formally registered, along with workers lacking protection (ILO, 2003), such as street vendors and individuals engaged in private businesses. This research aims to assess the status or profile of human capital about the participation of urban B40 women in the informal sector in Sabah. The study utilizes a sample-based approach, employing questionnaires to gather data from urban B40 women involved in informal sector activities, with a focus on descriptive analysis. The objective of this study is to unveil the average profile concerning education levels, attitudes toward training, and the impact of skills and experience on the participation of B40 women in the informal sector in Sabah. The results underscore the significance of programs that invest in human capital among B40 women, particularly in urban settings, as crucial contributors to enhancing the living standards of B40 women in Sabah.